Modern approaches to agent-based complex automated negotiation - Fujita, Katsuhide; Bai, Quan; Ito, Takayuki, 1972-; Zhang, Minjie (Computer scientist); Ren, Fenghui; Aydogan, Reyhan; Hadfi, Rafik (Springer, 2017)
This book addresses several important aspects of complex automated negotiations and introduces a number of modern approaches for facilitating agents to conduct complex negotiations. It demonstrates that autonomous negotiation is one of the most important areas in the field of autonomous agents and multi-agent systems. Further, it presents complex automated negotiation scenarios that involve negotiation encounters that may have, for instance, a large number of agents, a large number of issues with strong interdependencies and/or real-time constraints.
Keywords: Intelligent agents (Computer software); elektronické knihy; electronic books